Qualidade pós-colheita de frutos de abacaxis "Perola"e Turiaçu: influência das condições de armazenamento e avaliação sensorial - Pereira, Anna Paula Araújo (2013)
Given the large acceptance of the pineapple in domestic and international market, as well as the causes of low export of pineapple fruits ranging from the lack of standardization of fruit until the deficiency in knowledge of postharvest physiology of new cultivars capable of being inserted in the global market, we tried to present this work with the new cultivar 'Turiaçu', for that we sought to study and compare the physical, chemical and sensory characteristics of fruits of this cultivar to cultivar 'Pearl' at different stages of maturation to throughout the storage period. Among the variables analyzed, the more distinguished the two cultivars, with mean cultivar 'Turiaçu' was higher than were weight loss, SS content, acidity titutável and SS / TA ratio, which are of utmost importance with regard the quality of a product for marketing. The cultivar 'Turiaçu' showed average levels of SS throughout the storage process larger than the cultivar 'Pearl', as well as lower levels of acidity. However, it showed slightly higher average for the central cylinder of the fruits, the fruit pits not for marketing as the central axis, known as the stem is not discarded during consumption. The results show that the acceptance of samples of both cultivars by 91 tasters fell over on the seventh, eighth and ninth level of Hedonic Scale characterized respectively by "enjoyed regular", "beautiful" and "like very much", when more than 50% of the panelists gave notes greater than or equal to seven for all attributes